HUBUNGAN PERAN ORANGTUA DALAM MENJAGA KESEHATAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI ANAK - Susanti, Keny Erva (STIKES Widyagama Husada, 2025)
The most frequent dental health problem in children is dental caries. This condition has a significant impact on children's growth and development and affect their future. Parents' attitudes and behavior in maintaining dental health have a significant influence on children's behavior. The aim of this study was to determine the relationship between the role of parents in maintaining oral health and the incidence of children's dental caries. This study used a cross-sectional design. The sample in this research were students and parents at RA Muslimat NU 25 Malang City. The parents of these students were given a questionnaire, while the students underwent dental observation examinations. The sampling technique in this research is total sampling. The results showed that out of 49 parents who played a significant role in dental and oral health, 18 children were found to have caries. Of the 40 (81.6%) respondents on the role of parents in maintaining good oral health, there were 31 (63.3%) children who did not experience dental caries. According to Pearson correlation analysis, there is correlation between parents' role in maintaining oral health and the incidence of children's dental caries. With a correlation coefficient of -0.622, it falls into the strong correlation group, which means that the higher the parental involvement, the lower the level of dental caries. Understanding and active role of parents in maintaining children's dental health and how parents can be a good example, guide, direct, motivate, and supervise children in maintaining dental hygiene is important in preventing caries.